2014
DOI: 10.1155/2014/370696
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of V2O5 Nanoflakes on PET Fiber as Visible-Light-Driven Photocatalysts for Degradation of RhB Dye

Abstract: The visible-light-driven semiconductor photocatalysts are the current research focus techniques used to decompose organic pollutants/compounds. The photodegradation efficiency of organic compounds by photocatalyst is expected to be better compared to UV-light-driven semiconductor photocatalysts technique since the major components of our solar energy are visible light (∼44%). However, as most of the previous research work has been carried out using semiconductor photocatalysts in the form of powder, extra step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…This broadening of peaks is a result of reduced crystallinity of MnO 2 over V 2 CT x sheets. A small peak of V 2 O 5 near a 2Ө value of 42.7° can be observed, which is produced as a result of heat produced during the etching process [ 41 ]. Vanishing of the (002) diffraction peak with the increased weight percent of MnO 2 is a result of decreased crystallinity of the MnO 2 -V 2 CT x nanocomposites.…”
Section: Resultsmentioning
confidence: 99%
“…This broadening of peaks is a result of reduced crystallinity of MnO 2 over V 2 CT x sheets. A small peak of V 2 O 5 near a 2Ө value of 42.7° can be observed, which is produced as a result of heat produced during the etching process [ 41 ]. Vanishing of the (002) diffraction peak with the increased weight percent of MnO 2 is a result of decreased crystallinity of the MnO 2 -V 2 CT x nanocomposites.…”
Section: Resultsmentioning
confidence: 99%
“…6a (Rafique et al 2019b). It was observed that absorbance peak is decreased with passage of irradiation time due to cycloreversion process in which breakage of π* bond of rhodamine B by radicals occur ( 4) (Chan et al 2014). Figure 6a depicts that the catalyst is very efficient and presented high performance with increase in time of exposure.…”
Section: Effect Of Catalyst Contact-time Temperature Ph and Catalyst Loading On Photodegradation Of Rhbmentioning
confidence: 99%
“…In AOP, highly reactive radicals are generated that convert the organic pollutants into less hazardous products having potential to oxidize them. Many nanomaterials such as metal oxide semiconductors including zinc oxide (ZnO) (Aziz et al 2014;Chan et al 2013;Daneshvar et al 2007;Hong et al 2009;Xie et al 2011), titanium dioxide (TiO 2 ) (Chan et al 2014;Esfahani et al 2012;Smijs and Pavel 2011), Copper oxide (CuO) (Mehr et al 2018), Tungsten Oxide (WO 3 ) (Tahir et al 2018b) have been reported as wide band gap photocatalyst for degradation of pollutants under the Ultraviolet (UV) light. As the solar light spectrum contains 45% of visible light and less than 10% of UV light (Chan et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations